1975
DOI: 10.1212/wnl.25.10.980
|View full text |Cite
|
Sign up to set email alerts
|

Waldenstrom's macroglobulinemia and neuropathy

Abstract: Chronic idiopathic polyneuropathy of a primary demyelinating type developed in a man who had had recurrent herpes simplex 2 for 10 years. A serum IgM kappa M-component was demonstrated on the myelin of individual sural nerve fibers by direct immunofluorescence microscopy. Marrow lymphocytosis and serum M-component increased with time. Attempts to confirm antibody activity of the M-component were negative. The evidence suggests that the attachment of M-component to nerve is a physical-chemical one. Interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…No specific lesion of the nerve fiber has been identified in every case, and both axonal and myelin sheath abnormalities have been described. In a number of instances monoclonal immunoglobulins have been demonstrated immunohistochemically to have adhered to myelin in vivo { S , 12,17,22,23,271, to bind to myelin components or myelin itself in vitro { 11, 22), or both. Abnormal globulin has also been demonstrated in the endoneurial interstitium of one patient with immunoglobulin G, myeloma and cryoglobulinemia {251.…”
mentioning
confidence: 99%
“…No specific lesion of the nerve fiber has been identified in every case, and both axonal and myelin sheath abnormalities have been described. In a number of instances monoclonal immunoglobulins have been demonstrated immunohistochemically to have adhered to myelin in vivo { S , 12,17,22,23,271, to bind to myelin components or myelin itself in vitro { 11, 22), or both. Abnormal globulin has also been demonstrated in the endoneurial interstitium of one patient with immunoglobulin G, myeloma and cryoglobulinemia {251.…”
mentioning
confidence: 99%
“…Our indirect immunofluorescent studies ( Propp et al (1975), showed no such affinity. None of these nerves showed direct immunofluorescent staining (Table 1).…”
Section: Indirect Immunofluorescencementioning
confidence: 58%
“…1). (Propp et al, 1975;Hobbs et al, 1975), and in the endoneurium and perineurium (Chazot et al, 1974(Chazot et al, , 1976 in patients with Waldenstrom's macroglobulinaemia and peripheral neuropathy. In addition, monoclonal IgG and IgA has been found in nerve biopsy samples of patients with myeloma and peripheral neuropathy (Chazot et al.…”
Section: Indirect Immunofluorescencementioning
confidence: 99%
“…Although the etiology of this type of neuropathy remains unknown, the deposition of antibodies on the myelin sheaths of nerves (2)(3)(4)(5)(6)(7)(8) and the binding of IgM and IgG paraproteins to peripheral nerve myelin (6)(7)(8)(9)(10)(11)(12) suggest that the paraproteins play a causative role in neuropathy. Moreover, IgM paraproteins from some polyneuropathy patients have been found to react with human myelin-associated glycoprotein (MAG) by several groups (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%